Beyond the floor effect on the Wechsler Intelligence Scale for Children – 4th Ed. (WISC‐IV): calculating IQ and Indexes of subjects presenting a floored pattern of results. (1st July 2014) - Orsini, A.; Pezzuti, L.; Hulbert, S.
Abstract Background It is now widely known that children with severe intellectual disability show a 'floor effect' on the Wechsler scales. This effect emerges because the practice of transforming raw scores into scaled scores eliminates any variability present in participants with low intellectual ability and because intelligence quotient (IQ) scores are limited insofar as they do not measure scores lower than 40. Method Following Hessl et al.'s results, the present authors propose a method for the computation of the Wechsler Intelligence Scale for Children – 4th Ed. (WISC‐IV)'s IQ and Indexes in intellectually disabled participants affected by a floored pattern of results. The Italian standardization sample (n = 2200) for the WISC‐IV was used. The method presented in this study highlights the limits of the 'floor effect' of the WISC‐IV in children with serious intellectual disability who present a profile with weighted scores of 1 in all the subtests despite some variability in the raw scores. Results Such method eliminates the floor effect of the scale and therefore makes it possible to analyse the strengths and weaknesses of the WISC‐IV's Indexes in these participants. Conclusions The Authors reflect on clinical utility of this method and on the meaning of raw score of 0 on subtest.